(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Biology literacy is essential for understanding and addressing various health and environmental issues. Assessing the biology literacy level among adolescents can provide insights into the effectiveness of biology education and identify areas for improvement. This study aims to evaluate the biology literacy level among adolescents in the Port Harcourt Metropolis, Rivers State, Nigeria. A cross-sectional survey was conducted from January to June 2024, involving 400 adolescents aged 13-18 years from ten secondary schools in the Port Harcourt Metropolis. Participants completed a standardized biology literacy test covering key concepts such as cell biology, genetics, ecology, and human physiology. Data were analyzed using descriptive statistics and inferential analysis to determine the overall literacy level and identify factors influencing biology literacy. The findings revealed that the average biology literacy score among the adolescents was 58%, indicating a moderate level of understanding. Significant differences were observed based on gender, with females scoring higher (62%) compared to males (54%). Additionally, students from private schools demonstrated higher literacy levels (65%) compared to those from public schools (51%). Factors such as study habits, access to learning resources, and teacher quality were found to significantly influence biology literacy levels. The study highlights the need for targeted interventions to improve biology literacy among adolescents in the Port Harcourt Metropolis. Enhancing teacher training, providing adequate learning resources, and promoting effective study habits are crucial steps. Policymakers and educators should focus on these areas to ensure that students acquire the necessary biology knowledge and skills to address health and environmental challenges.